Understanding the Reducibility of CeO 2 Surfaces by Proton-Electron Transfer from CpCr(CO) 3 H - Bunjaku, Osman; Florenski, Jan; Wischnat, Jonathan; Klemm, Elias; Safonova, Olga V; van Slageren, Joris; Estes, Deven P (Inorganic chemistry, 2024)
CeO is a popular material in heterogeneous catalysis, molecular sensors, and electronics and owes many of its special properties to the redox activity of Ce, present as both Ce and Ce . However, the reduction of CeO with H (thought to occur through proton-electron transfer (PET) giving Ce and new OH bonds) is poorly understood due to the high reduction temperatures necessary and the ill-defined nature of the hydrogen atom sources typically used. We have previously shown that transition-metal hydrides with weak M-H bonds react with reducible metal oxides at room temperature by PET. Here, we show that CpCr(CO) H ( ) transfers protons and electrons to CeO due to its weak Cr-H bond. We can titrate CeO with and measure not only the number of surface Ce sites formed (in agreement with X-ray absorption spectroscopy) but also the lower limit of the hydrogen atom adsorption free energy (HAFE). The results match the extent of reduction achieved from H treatment and hydrogen spillover on CeO in a wide range of applications.